The Experiences of Intensive Care Nurses During the COVID-19 Crisis in Turkiye: A Qualitative Study - Eda Kes; Duygu Kes (Genel Tıp Dergisi)
Background/Purpose: This study aimed to investigate the experiences of intensive care nurses who provided care for COVID-19 patients during the pandemic period. Methods: This study is a descriptive phenomenological study with thematic analysis. Semi-structured interviews were conducted with 10 intensive care nurses in a pandemic hospital which has a total of seven intensive care units with a capacity of 88 beds in northwestern Turkey. Results: Five main themes and 13 sub-themes emerged from the analysis. The main themes were Professional relations, working conditions, safety, nursing care and psychological aspect. Conclusion: Intensive care nurses are experiencing intense emotional burden, fear of the unknown, perception of insufficiency and increased workload during the COVID-19 pandemic. Nursing care has been affected by the changes in the course of the disease and isolation.